Online Self-Regulatory Learning Behaviors as a Mediator in the Relationship between Online Course Perceptions with Achievement - Barnard, Lucy; Paton, Valerie; Lan, William (International Review of Research in Open and Distributed Learning, 2008)
Positive perceptions of online course communication and collaboration have been associated with better academic outcomes, while self-regulatory learning behaviors have also been linked to academic achievement and other positive learning outcomes. In the current study, we examined whether self-regulatory learning behaviors may be considered as mediating the relationship between student perceptions of online course communication and collaboration with academic achievement as measured by grade point average (GPA). Results indicate that online self-regulatory learning behaviors, though not strongly associated with academic achievement in and of themselves, do mediate the positive relationship between student perceptions of online course communication and collaboration with academic achievement.